Career information, career counseling, and career development - Brown, Duane (Boston : Pearson,A&B, 2003)
This book is intended to help those who are now engaged, or who expect to be engaged, in facilitating the career development process. It is written expressly with school counselors, rehabilitation counselors, counseling psychologists, employment counselors, placement officers, and career counselors in mind. However, teachers, media specialists, social workers, and others who are influential in the career development process can benefit from the contents of the book.-Pref.
Includes bibliographical references and index.
Keywords: Vocational guidance; Bibliography; Information service; Information storage and retrieval systems